Methodology of echocardiographic analysis of morphological variations of the aortic arch and its branches in children – own experience - Wojciech Mądry; Ewa Zacharska-Kokot; Maciej A. Karolczak (Journal of Ultrasonography, 2019)
We wish to share our experience in echocardiographic assessment of the course of the aortic arch, illustrating it with multiple examples of the majority of possible variants. The course of the aortic arch and its branches may be visualized using high parasternal and suprasternal views in sagittal and transverse planes. It is hardly ever possible to visualize the entire aortic arch on a single ultrasonographic section, particularly in the case of pathological variations. Echocardiography should be performed in a dynamic mode, as in the case of CT angiography or magnetic resonance, by gradually moving the ultrasound beam and following the position of subsequent aortic segments and branches on the screen. Due to disturbances in ultrasound propagation caused by air-containing tissues, such as the trachea, bronchi and lungs as well as bones (sternum and ribs), each evaluation of the entire arch requires the use of a higher number of echocardiographic views. The presented data show that echocardiographic detection of the main details of aortic arch anomalies is possible in practically all cases. In the case of patients considered for surgical treatment, all unresolved issues should be clarified with CT angiography or MRI, enabling 3 dimensional reconstruction of vessels and other thoracic structures. Knowledge of the main elements of an abnormal arch is crucial for proper planning of this type of examination; therefore the diagnostic process should be always initiated with echocardiography. Echocardiography is often sufficient to answer all clinical questions and finalize the diagnostic process.